2008
DOI: 10.1128/jb.01055-08
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Combination of Genetic Systems for the Synthesis of Trehalose in Rubrobacter xylanophilus : Properties of a Rare Actinobacterial TreT

Abstract: Trehalose is the primary organic solute inRubrobacter xylanophilus under all conditions tested, including those for optimal growth. We detected genes of four different pathways for trehalose synthesis in the genome of this organism, namely, the trehalose-6-phosphate synthase (Tps)/trehalose-6-phosphate phosphatase (Tpp), TreS, TreY/TreZ, and TreT pathways. Moreover, R. xylanophilus is the only known member of the phylum Actinobacteria to harbor TreT. The Tps sequence is typically bacterial, but the Tpp sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 40 publications
(77 reference statements)
6
33
0
Order By: Relevance
“…The enzyme displayed maximum activity at 65°C (Fig. 4B), which is in good agreement with the optimum growth temperature of R. xylanophilus and similar to that of other enzymes from this bacterium (15,16). An Arrhenius plot showed that the activation energy of the reaction was approximately constant in the temperature range from 30°C to 50°C, and the activation energy was calculated as 62.1 kJ/mol (see Fig.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The enzyme displayed maximum activity at 65°C (Fig. 4B), which is in good agreement with the optimum growth temperature of R. xylanophilus and similar to that of other enzymes from this bacterium (15,16). An Arrhenius plot showed that the activation energy of the reaction was approximately constant in the temperature range from 30°C to 50°C, and the activation energy was calculated as 62.1 kJ/mol (see Fig.…”
Section: Resultssupporting
confidence: 69%
“…Such differences have also been reported for other genes from R. xylanophilus (16), indicating the necessity for reanalyzing the genome sequence. Interestingly, the amino acid sequence of RxDAO showed a higher identity to hypothetical proteins of the phylogenetically distant Gram-negative bacteria S. aurantiaca and M. stipitatus than that of DAOs of phylogenetically close Gram-positive bacteria S. coelicolor and A. protophormiae.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The recombinant TPP Vmax was 290.0 ± 3.79 µmol.min -1 , and K M was 3.19 ± 0.10 mM, which is on the same order of magnitude of most of the reported TPPs: 2.5 ± 0.1 mM (Seo et al, 2000), 1.5 mM (Silva et al, 2005), 6.1 ± 1.5 mM (Nobre et al, 2008), 0.42 mM (Kushwaha et al, 2011), 0.39 ± 0.16 mM (Li et al, 2012), 0.36 ± 0.06 mM (Farelli et al, 2014), 0.87± 0.06 mM (Miao et al, 2016), 0.48 mM (Shan et al 2016), 0.23 ± 0.07, 0.50 ± 0.10, 0.69 ± 0.07 and 0.31 ± 0.04 mM (Liu et al, 2017a).…”
Section: Resultssupporting
confidence: 60%
“…S4 in the supplemental material), with Acidithio-bacillus species displaying Fe 3ϩ sensitivity and Rubrobacter species having an affinity for ferric iron. Although high concentrations of ferric iron can lead to oxidative stress on microbes (71), several strategies, including the synthesis of trehalose (72) and radioresistance mechanisms (73)(74)(75), have been found in Rubrobacter species to resist oxidative stress. Second, patterns of Ferroplasma and Leptospirillum abundance were apparently shaped by tailing pH.…”
Section: Discussionmentioning
confidence: 99%